Evaluation of inflammatory markers as prognostic factors in the treatment of hepatocellular carcinoma (HCC) with degradable starch microspheres by transarterial chemoembolization (DSM-TACE) - Steinberg, Hannah Luisa; Tropotel, Andriana; Theysohn, Jens M.; Schaarschmidt, Benedikt; Haubold, Johannes; Jeschke, Matthias; Jochheim, Leonie; Ludwig, Johannes Maximilian (Cancers, 2025)
Objective: To evaluate the prognostic value of pre-therapeutic inflammatory markers before transarterial chemoembolization with degradable starch microspheres (DSM-TACE) in the treatment of hepatocellular carcinoma (HCC). Methods: A total of 155 patients (81% male, median age: 68 years) who underwent first-time DSM-TACE between 07/13 and 06/22 were included in the study. Inflammatory indices were dichotomized using median values. Cox proportional hazard model for univariate (UVA) and multivariate (MVA) analyses (hazard ratio; 95% CI, p-value) and Kaplan-Meier analyses (overall survival (OS) in months; 95% CI; log-rank test) were performed. Results: The median OS of the study cohort was 15.9 (12.9-20) months with a median survival according to BCLC stages A (12%), B (41%), and C (47%) of median not reached, 19.3 (15.3-27), and 7.2 (4.5-9.0) months, respectively (p < 0.0001). In the UVA, several inflammatory markers on OS were statistically significant with the systemic inflammatory response index (SIRI; ≤median (2.04) HR: 0.41 (0.19-0.89); p = 0.024) and the lymphocyte to monocyte ratio (LMR; >median (1.82) HR: 0.44 (0.2-0.9); p = 0.025) remaining statistically significant in MVA together with the BCLC stage (p = 0.0001), ALBI grade (p = 0.016), hepatic tumor burden (≤25% vs. >25%; p = 0.006), and largest HCC lesion (≤5.5 cm vs. >5.5 cm; p = 0.008). In subgroup analysis, patients with elevated LMR and reduced SIRI exhibited significantly prolonged overall survival (OS) in both BCLC B (p < 0.0001) and Child-Pugh A (p = 0.021) subgroups. Conclusion: The findings suggest that SIRI and LMR may serve as valuable tools in identifying BCLC B and Child-Pugh A patients who could potentially benefit better from DSM-TACE treatment. Nevertheless, further research is recommended to confirm these findings and to provide more comprehensive insights.
Gesehen am 22.07.2025